PERSEPSI TERHADAP KEBIASAAN MENONTON ANIME DENGAN KEMAMPUAN MENYIMAK MAHASISWA ANGKATAN 2019 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - M. Syahru Luthfi; Hadriana Hadriana; Merri Silvia Basri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research was conducted to see the perception of students' anime viewing habits on students' listening skills. The sample of this study is the entire population of Japanese Language Education students for the Class of 2019. The instruments used are the distribution of questionnaires and students' speaking ability tests. The distribution of questionnaires and listening ability tests were carried out to see if the habit of watching anime would affect students' listening skills.Key Words: Watching Anime, Listening Skills